Al-Uqud Al-Murakkabah Pada Transaksi Online Dengan Sistem Gofood Dalam Perspektif Fikih Muamalah - Inayah, Khayu; Hamid, Abdul; Afifah, Nur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The Gofood service or feature in the Gojek applications is a transaction service or buying and selling of food between customers and restaurans or sellers through drivers on the Gojek application. Online services provided by the Gojek application are online buying and selling transactions with the Gofood system where there are two types of contracts carried out in one transaction, namely transactions with wakalah contracts and transactions with ijarah contracts. In this study, the authors use qualitative research or field research by collecting information directly from the object of research through interviews and documents. The data sources in this study are Gojek drivers and customers of the Gojek application, service feature. The results of this study indicate that the implementation of al-uqud al-murakkabah fulfills. In this study, the formulation of the problem is: what is the mechanism for implementing Al-Uqud Al-Murakkabah in online transactions with the Gofood system and how is the mechanism for implementing Al-Uqud Al-Murakkabah in online transactions with the Gofood system in the perspective of muamalah fiqh. the pillars and conditions in the wakalah and ijarah contracts in the perspective of Muamalah fiqh.